ANALISA SIFAT MEKANIK PENGARUH VARIASI PERENDAMAN DAN PENEKANAN PADA KOMPOSIT BERBAHAN SERAT BUNDUNG - sutrisno, sutrisno; Azmal, Azmal (Faculty of Engineering, Universitas Tanjungpura, 2020)
This study aims to determine the effect of mechanical properties of impact, bending and tensile of bundle fiber composites with 5% NaOH variation of immersion time 0.5 hours, 1 hour and 1.5 hours. Then the blending and casting process is carried out to form a composite material with 20% fiber and 80% resin binder with a catalyst content of 1% and pressurized with press variations of 5 kg, 10 kg and 15 kg. The results of the blending and casting process are made according to the testing standard and then testing the mechanical properties. Impact, bending and tensile strength test results showed that immersion of 0.5 hours with 15 Kg concentration produced the highest value, namely Impact strength 94.89 J / mm2, bending strength 17.77 N / mm2 and tensile strength 27 N / mm2. Whereas the fracture form of the composite is the binding and fiber breaking evenly at the same point and the fiber is not pulled from the metric.